2003
DOI: 10.4102/sajhrm.v1i3.28
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution Of Co-Operative Education In The Growing Of Talent In South Africa: A Qualitative Phenomenological Exploration

Abstract: Organisational talent is internationally regarded a key success factor in a competitive world and is continuously challenged. In South Africa, the Apartheid heritage further presents major challenges regarding developmental opportunities of talented people. Co-operative education presents, as structured educational strategy that progressively integrates academic study with learning through productive work experiences, itself as a means to grow the talent of the South African people. As result of the inadequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…A feature of in-depth interviews, such as those carried out by Legard et al (2003), is their potential for being generative because they encourage the articulation of independent responses, which reflect the knowledge and understanding of the interviewee. In this case, an in-depth qualitative questionnaire was considered as the most appropriate data collection method (Groenewald, 2003).…”
Section: Methodological Framework Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A feature of in-depth interviews, such as those carried out by Legard et al (2003), is their potential for being generative because they encourage the articulation of independent responses, which reflect the knowledge and understanding of the interviewee. In this case, an in-depth qualitative questionnaire was considered as the most appropriate data collection method (Groenewald, 2003).…”
Section: Methodological Framework Of the Studymentioning
confidence: 99%
“…The data were analysed in descriptive terms and presented as generalised descriptions with selected individual responses as examples. According to Groenewald (2003), studies influenced by phenomenology should aim to provide a description of human experience as it is experienced by the person herself or himself (Bentz & Shapiro, 1998, cit. in Groenewald, 2003.…”
Section: Methodological Framework Of the Studymentioning
confidence: 99%
“…However, it is worth mentioning that research around the relationship between theoretical education and practical experience has been done in abundance providing clarity on roles of stakeholders in WIL (Yiu and Law, 2012;Stanley, 2005;Choy and Delahaye, 2011). The same can be said about research done on the benefits of WIL (Weible, 2010;Pitout, 2009;Zopiatis and Theocharous, 2013;Rudman and Terblanche, 2012;Leslie and Richardson, 2000), research on expectations of WIL (Cannon and Arnold, 2010;Kelley-Patterson and George, 2001;Stone and McLaren, 1999;Emslie, 2009), perceptions of WIL (Petrillose and Montgomery, 1998;Lam and Ching, 2007;Ross and Elechi, 2002;Kay and DeVeau, 2013;Cho, 2006;Tse, 2010;Beggs et al, 2008) and the contribution of WIL (Walo, 2001;Zopiatis, 2007;Groenewald and Schurink, 2003). The results of all these studies can be summed-up as providing useful information about WIL in areas identified above but all these studies fall short in assessing the supervisor's assessments of WIL and students' analysis of their own WIL experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In keeping with the methodology for data explicitation of Groenewald and Schurink (2003), the term "explicitation" has replaced the term "analysis" on Hycner's (1999, p. 161) recommendation. Hycner (1999, p. 161) argues that the term "analysis" has dangerous connotations for phenomenology in that it implies a "'breaking into parts' and therefore often means a loss of the whole phenomenon".…”
Section: Data Explicitationmentioning
confidence: 99%
“…Data explicitation thus took place within a phenomenological paradigm, as used by Groenewald and Schurink (2003) …”
Section: Data Explicitationmentioning
confidence: 99%